CMV specific T cell immune response in hepatitis C negative kidney transplant recipients receiving transplant from hepatitis C viremic donors and hepatitis C aviremic donors. Issue 1 (31st December 2022) - Azhar, Ambreen; Tsujita, Makoto; Talwar, Manish; Balaraman, Vasanthi; Bhalla, Anshul; Eason, James D.; Nouer, Simonne S.; Sumida, Keiichi; Remport, Adam; Hall, Isaac E.; Griffin, Randi; Rofaiel, George; et al.
Abstract: Kidney transplants (KT) from hepatitis C (HCV) viremic donors to HCV negative recipients has shown promising renal outcomes, however, high incidence of cytomegalovirus (CMV) viremia were reported. We performed a prospective cohort study of 52 HCV negative KT recipients from Methodist University Hospital including 41 receiving transplants from HCV aviremic donors and 11 from HCV viremic donors. CMV specific CD4+ and CD8 + T cell immunity was measured by intracellular flow cytometry assay. Primary outcome was the development of positive CMV specific CD4+ and CD8 + T cell immune response in the entire cohort and each subgroup. The association between donor HCV status and CMV specific CD4+ and CD8 + T cell immune response was analyzed by Cox proportional hazard models. Mean recipient age was 48 ± 13 years, with 73% male and 82% African American. Positive CMV specific CD4+ and CD8 + T cell immune response was found in 53% and 47% of the cohort at 1 month, 65% and 70% at 2 months, 80% and 75% at 4 months, 89% and 87% at 6 months, and 94% and 94% at 9 months post-transplant, respectively. There was no significant difference in the incidence of positive CMV specific T cell immune response between recipients of transplants from HCV aviremic donors compared to HCV viremic donors in unadjusted (for CD8+: HR = 1.169, 95%CI: 0.521–2.623; for CD4+: HR = 1.208, 95%CI: 0.543–2.689) and adjusted (for CD8+: HR = 1.072, 95%CI: 0.458–2.507; for CD4+: HR = 1.210, 95%CI: 0.526–2.784) Cox regression analyses. HCV viremia in donors was not associated with impaired development of CMV specific T cell immunity in this cohort.